A multiple integrated approach for modelling critical success factors in sustainable LSS implementation. (December 2020) - Swarnakar, Vikas; Singh, A.R.; Antony, Jiju; Kr Tiwari, Anil; Cudney, Elizabeth; Furterer, Sandra
Highlights: Sustainability adds economic, social, and environmental dimensions to LSS. Many organizations struggle with the obstacles faced when implementing LSS. A sustainable LSS framework enables organizations to reduce risks timely. MICMAC can be effectively used to analyze the nature of critical success factors. Abstract: Manufacturing organizations have struggled with sustaining their Lean Six Sigma programs for operational excellence. This study was performed to identify critical success factors necessary for sustaining organizations' Lean Six Sigma programs. The research study methodology included: 1) surveying subject matter experts with an open-ended questionnaire approach to identify critical success factors; 2) applying a total interpretive structural modeling (TISM) technique to develop a structural hierarchical interrelation-based model to identify the relationships between the critical factors; 3) integrating fuzzy theory with a Matriced Impacts Croisés Multiplication Appliquée á un Classement (MICMAC) approach to analyze the nature of the critical success factors; and finally 4) validating the structured hierarchical model through application of the structural equation modelling technique. Twenty-nine critical success factors for sustainable Lean Six Sigma were identified, categorized, and prioritized in this research. Management involvement to execute sustainable Lean Six Sigma in an organization and structured sustainable Lean Six Sigma implementation training were identified in this study as the most significant success factors of the twenty-nine factors for successful sustainable Lean Six Sigma implementation. This study provides an essential reference for decision-makers, policymakers, researchers, and practitioners by modeling and validating the interrelationship of critical success factors for Lean Six Sigma implementation. This paper provides a detailed description of the research methodology to enable other researchers and practitioners to perform the same method in other organizations by identifying and extending the set of critical success factor groups.